Extensive bone marrow infiltration and abnormal free light chain ratio identifies patients with asymptomatic myeloma at high risk for progression to symptomatic disease - Kastritis, E.; Terpos, E.; Moulopoulos, L.; Spyropoulou-Vlachou, M.; Kanellias, N.; Eleftherakis-Papaiakovou, E.; Gkotzamanidou, M.; Migkou, M.; Gavriatopoulou, M.; Roussou, M.; Tasidou, A.; Dimopoulos, M.A. (Leukemia, 2013)
Asymptomatic multiple myeloma (AMM) is characterized by a constant risk of progression to symptomatic myeloma. To evaluate previously recognized risk factors and to identify high-risk features we analyzed 96 patients with AMM and at least 18 months of follow-up. The progression rate at 1,2, and 3 years was 8%, 15% and 26%, respectively, and the projected 5-year progression rate was 38%. Extensive bone marrow (BM) infiltration, abnormal free light chain (FLC) ratio and serum monoclonal (M)-protein≥3 gr/dl were the most significant factors for progression, whereas the type of heavy (IgG vs IgA) or light chain or immunoparesis of the uninvolved immunoglobulins were not. Abnormal marrow signal of magnetic resonance imaging of the spine was associated with a significant risk of progression (median 15 months, P=0.001). Extensive BM infiltration ≥60% (hazard ratio, HR: 13.7, P<0.001) and FLC ratio≥100 (HR: 9, P=0.003) independently identified a 'very high-risk' group, which included 12.5% of patients with AMM and who progressed ≤18 months from initial diagnosis. Development of anemia and/or lytic bone lesions were the most common features of symptomatic progression. In conclusion, there is a subgroup of patients who have a substantial risk of progression to symptomatic disease that can be detected at diagnosis (either by extensive BM infiltration≥60% or FLC ratio≥100) and may be considered for immediate treatment. © 2013 Macmillan Publishers Limited All rights reserved.
Keywords: bone marrow; free light chains; immunoparesis; Risk; Smoldering myeloma; trephine biopsy